From Wheelchair to Cane: Elective Transtibial Amputations in a Patient with Spina Bifida. (November 2015) - Mayo, Amanda; Berbrayer, David
Abstract : ABSTRACT: Spina bifida is associated with foot deformities, which may lead to foot ulcers, osteomyelitis, and limb amputation. Calcanectomy and Symes amputations have been reported successful in spina bifida. There is lack of evidence for transtibial amputations. This case describes a 27-yr-old woman with L4 level spina bifida who underwent bilateral transtibial amputations. She ambulated with bilateral ankle foot orthoses and canes until age 22. At age 22, she had bilateral foot reconstructive surgeries complicated by nonunion, ulcerations, and osteomyelitis. She was using a wheelchair by age 25. She had elective bilateral transtibial amputations at age 27 for progressive osteomyelitis. Four weeks after amputations, she was fit with bilateral prostheses. On completion of 2 mos of rehabilitation, she ambulated with a cane. This case demonstrates good functional outcomes after transtibial amputations in a young spina bifida patient. Prosthetic fitting should be considered for similar, previously high functioning spina bifida patients with transtibial amputation(s).